Determinants in Investment Behaviour During The COVID-19 Pandemic - Kiruba, Angelin S.; Vasantha, Vasantha (The Indonesian Capital Market Review, 2021)
This study investigated the psychological behaviour of investors in the stock market during the period of COVID-19. The survey was conducted between April and June 2020, following the lockdown announcement of the Indian Government on 25th March. There were 400 respondents. This paper has attempted to identify the impact on psychological behaviour during the initial stage of COVID-19 in India. The collected data has been used to determine the psychological factors which may have influenced investment decisions. The statistical tools of Cronbach Alpha, factor analysis, descriptive analysis, and multiple regression techniques were applied using the SPSS 21 package. The study has analysed the psychological dimensions of the behaviour when responding to fear, risk perception, risk propensity, investors’ anxiety to market volatility, herding and vaccination updates. The results show that the behavioural response to fear, risk perception, herding and vaccination updates have influenced investors’ decision-making during the COVID-19 pandemic.